(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article presents a comprehensive analysis of the historical, architectural, and ecological significance of tangible cultural heritage sites located in the Forish District of Jizzakh Region, Republic of Uzbekistan. Particular attention is given to the Hazrati Zaynulobiddin religious–architectural complex and unique heritage monuments situated in the village of Mojrum (Majrum). Based on contemporary scholarly approaches, the study examines key issues related to the preservation and protection of these sites, their digital passportization, and the prospects for developing pilgrimage and ecotourism as of 2025. Special emphasis is placed on the role of these heritage sites within the framework of sustainable development and the conservation of the cultural landscape of the Nuratau region.